A verificação de fatos e prognoses jurídico-legislativos no controle de constitucionalidade brasileiro - Torres, João Guilherme Gualberto (2018)
In the paradigm of Rule of Law, the constitutional jurisdiction becomes more important by promotion partnership democracy. This takes place by the defense of fundamental rights present in the Brazilian Constitution and by the safeguard of minorities’ interests, sometimes violated by the seasonal majorities. The judicial review becomes an indispensable mechanism for the pursuit of state purposes whenever the agents of the “Power”, owned by the People, disengage from the promotion of the welfare state. The verification of legislative facts and prognosis is one of the mechanisms available to the Constitutional Court to investigate the validity of the statutes and to deem them unconstitutional if that is the case. The analysis by the Judiciary considers whether the Legislative, at the time of legislative procedure, had sufficient knowledge to elaborate the Acts and if it could foresee the consequences of its execution. A legislative procedure that does not observe fundamental rights and guarantees violates the social contract and turns legal norms unconstitutional. Based on linguistic turn and the philosophy of language in the Law some dogmas must be overcome otherwise it will never fulfill the constitutional promises. The constitutional proceeding opens to the facts and techniques of popular participation, with the constitutional interpretation aided by an “open society of constitutional interpreters”, to achieve constitutional answers in rational and wellgrounded decisions by the substantive adversarial principle. In the absence of specific legislation, the Brazilian Acts 9.868/99 and 9.882/99 must be adapted of this paradigm and the mechanisms of Brazilian Civil Procedure Code should be used. The bibliographic review and the analysis of the decisions issued by the Brazilian Constitutional Court give the necessary instruments for the systematization of the study, the entry incongruences and the overcoming of old practices.